Hasil dan kualitas benih kedelai pada pola tanam bersisipan dan beruntun - Rudi Hartawan; Yulistiati Nengsih; Adilla Adistya; Edy Marwan (Jurnal Agro, 2023)
Sequential and continuous cropping patterns are strategy to increase efficiency in soybean seed production. The research aimed to determine the impact of cropping patterns on yield and quality, also to obtain efficiency of manpower, nutrient and planting duration of soybean seed production. The research was conducted from January to October 2019. Soil fertility and compost  analysis  was  done  at  Center  for  Research  and  Development  of  Agricultural Land Resources, Bogor. Field research was at Sebapo experimental station. Proximate analysis was carried out at Center for Agricultural Postharvest Research and Development, Bogor. Seed testing was at Basic Laboratory of Batanghari University, Jambi. The research used completely randomized design with three replications. The treatment was cropping pattern: P0= standard, P1= sequential and P2= continuous. The variables observed were seed yield and quality, efficiency of manpower, nutrient and planting duration. The results showed that the seed yield of continuous cropping pattern decreased 16% and the sequential cropping pattern decreased 7.5%. The continuous cropping pattern increased manpower efficiency 22.88%, nutrient 75.30%, and planting duration 14.63%. The sequential cropping pattern increased manpower efficiency 8.25%, nutrient 75.35%, and planting duration 6.82%. The cropping pattern increased the efficiency of cultivation and did not affect the quality of soybean seed so that it can be used in soybean seed production.